Pemanfaatan Teknologi Artificial Intelligence (AI) Dalam Menghadapi Tantangan Mengajar Guru di Era Digital - Joupy G. Z. Mambu; Dedek Helida Pitra; Aziz Rizki Miftahul Ilmi; Wahyu Nugroho; Natasya V. Leuwol; Andi Muh Akbar Saputra (Departement of Mathematics Education, 2023)
This article aims to review the use of Artificial Intelligence (AI) technology in dealing with teachers' teaching challenges in the digital era. The digital age has rapidly changed the educational landscape, affecting the roles and tasks of teachers. They are faced with new challenges, such as managing an abundance of information, adapting teaching styles to individual needs, and providing effective feedback to students. In the face of these challenges, AI technology offers significant potential. This article will outline several ways in which AI technology can be utilized in the context of education. First, AI can assist teachers in managing data and information by using advanced algorithms to analyze and interpret student data. Second, AI technology can support the personalization of learning. Third, AI can be used to provide effective feedback to students. However, there are some challenges that may arise in the utilization of AI technology in the context of education. One of them is the concern about student data privacy and security. In addition, it is also important to consider that AI technology cannot completely replace the role of teachers, but only serves as a powerful tool. In conclusion, the utilization of AI technology can provide significant benefits for teachers in facing challenges in the digital era. By utilizing AI, teachers can manage data more efficiently, provide personalized learning, and provide effective feedback to students. However, it is important to keep in mind the limitations and challenges associated with the use of AI technology in education.